2011
DOI: 10.1523/jneurosci.0079-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Blockade Reduces the Opportunity Cost at Which Rats Maintain Operant Performance for Rewarding Brain Stimulation

Abstract: There is ample evidence that blockade of CB1 receptors reduces reward seeking. However, the reported effects of CB1 blockade on performance for rewarding electrical brain stimulation stand out as an exception. By applying a novel method for conceptualizing and measuring reward seeking, we show that AM-251, a CB1 receptor antagonist, does indeed decrease performance for rewarding electrical stimulation of the medial forebrain bundle in rats. Reward seeking depends on multiple sets of variables, including the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 57 publications
3
49
2
Order By: Relevance
“…The neuromodulator dopamine is of particular interest. Previous macroscopic analyses from pharmacological and drugs of addiction studies have revealed that an increase in the tonic release of the neuromodulator dopamine shifts the three-dimensional relationships towards longer prices [21][22][23], as if, for instance, dopamine multiplies the intensity of the reward. Equally, models of instrumental vigour have posited that tonic dopamine signals the average reward rate, thus realizing the opportunity cost of time [24,67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuromodulator dopamine is of particular interest. Previous macroscopic analyses from pharmacological and drugs of addiction studies have revealed that an increase in the tonic release of the neuromodulator dopamine shifts the three-dimensional relationships towards longer prices [21][22][23], as if, for instance, dopamine multiplies the intensity of the reward. Equally, models of instrumental vigour have posited that tonic dopamine signals the average reward rate, thus realizing the opportunity cost of time [24,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…This decision has been studied by economists [1][2][3][4][5], behavioural psychologists [6][7][8][9][10][11][12][13][14][15][16], ethologists [17] and neuroscientists [18][19][20][21][22][23][24]. Tasks involving free-operant behaviour are particularly revealing, because subjects can choose what, when and how, minimally encumbered by direct experimenter intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The model and associated three-dimensional (3D) measurement strategy have been used in previous studies to differentiate between actions of experimental manipulations on early and late stages of reward processing [21][22][23][24][25][26][27]. In the early versions of the model, perfect frequency following was assumed.…”
Section: Inferring the Physiological Properties Of The Substrate Undementioning
confidence: 99%
“…In the cases of rats GBR11-GBR14, each drug session included a complete survey of the mountain. In these cases, the data were resampled by survey (Hernandez et al, 2010;Trujillo-Pisanty et al, 2011). For example, 10 drug sessions were run with rat GBR11.…”
Section: Behavioral Experimentsmentioning
confidence: 99%
“…ICSS is typically measured in the curve-shift (Edmonds and Gallistel, 1974;Edmonds and Gallistel, 1977;Miliaressis et al, 1986) or progressive-ratio (Hodos, 1961) paradigm. It has been demonstrated recently (Arvanitogiannis and Shizgal, 2008;Hernandez et al, 2010;Trujillo-Pisanty et al, 2011) that neither method provides sufficient isolation of the different processes underlying reward seeking to distinguish between competing hypotheses concerning the variables to which dopamine neurons contribute, which include the sensitivity and gain of brain reward circuitry (Hernandez et al, 2010) and subjective effort cost (Salamone et al, 2005;Niv et al, 2007).…”
Section: Introductionmentioning
confidence: 99%